Probable slow slips in the mid-crust of Hsinchu, northwestern Taiwan: Temporal correlation between normal faulting earthquakes and relative uplift. (15th May 2016) - Pu, H.C.; Lin, C.H.
Highlights: Slow slip is consistently detected both on surface and in the upper crust. Faulting mechanisms repeatedly alternated in the survey area. Crustal deformation has the similar variation as faulting mechanisms do. Abstract: To investigate the seismic behavior of crustal deformation, we deployed a dense seismic network at the Hsinchu area of northwestern Taiwan during the period between 2004 and 2006. Based on abundant local micro-earthquakes recorded at this seismic network, we have successfully determined 274 focal mechanisms among ∼1300 seismic events. It is very interesting to see that the dominant energy of both seismic strike-slip and normal faulting mechanisms repeatedly alternated with each other within two years. Also, the strike-slip and normal faulting earthquakes were largely accompanied with the surface slipping along N60°E and uplifting obtained from the continuous GPS data, individually. Those phenomena were probably resulted by the slow uplifts at the mid-crust beneath the northwestern Taiwan area. As the deep slow uplift was active below 10 km in depth along either the boundary fault or blind fault, the push of the uplifting material would simultaneously produce both of the normal faulting earthquakes in the shallow depths (0–10 km) and the slight surface uplifting. As the deep slow uplift was stop, instead, the strike-slip faulting earthquakes would be dominated as usual due to strongly horizontal plate convergence in the Taiwan. Since the normal faulting earthquakes repeatedly dominated in every 6 or 7 months between 2004 and 2006, it may conclude that slow slip events in the mid crust were frequent to release accumulated tectonic stress in the Hsinchu area.